2017
DOI: 10.1371/journal.pone.0179729
|View full text |Cite
|
Sign up to set email alerts
|

Redifferentiation of aged human articular chondrocytes by combining bone morphogenetic protein-2 and melanoma inhibitory activity protein in 3D-culture

Abstract: Melanoma inhibitory activity (MIA) affects the differentiation to hyaline cartilage and can inhibit the osteogenic potential of bone morphogenetic protein (BMP)-2 in mesenchymal stem cells (MSC). The aim of this study was to investigate if MIA also inhibits the osteogenic potential of BMP-2 in human articular chondrocytes during redifferentiation, which may lead to a higher grade of differentiation without calcification. HAC of four female patients (mean age: 73.75 ±6.98) were seeded into 3D culture for 28 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…ACAN, COL2A1, and GAG are known to be the most components of cartilage ECM. In vitro, ACAN, COL2A1, and GAG biosynthesis support chondrocyte redifferentiation [41]. Therefore, changes in ACAN, COL2A1, and GAG reflect the anabolism of cartilage ECM.…”
Section: Discussionmentioning
confidence: 99%
“…ACAN, COL2A1, and GAG are known to be the most components of cartilage ECM. In vitro, ACAN, COL2A1, and GAG biosynthesis support chondrocyte redifferentiation [41]. Therefore, changes in ACAN, COL2A1, and GAG reflect the anabolism of cartilage ECM.…”
Section: Discussionmentioning
confidence: 99%
“…25 Although the use of BMP2 has been related to hypertrophy of chondrocytes and calcification of cartilage ECM associated with increased expression of COL10 mRNA and protein, [26][27][28] Payr et al have argued that hypertrophy and expression of osteogenic markers after BMP2 stimulation might be more relevant when using MSCs than human articular chondrocytes. 29 Still, the role played by BMP2 in the CDMB deserves further investigation. With respect to IGF1, a study on the redifferentiation capacity of human chondrocytes in pellet cultures has shown that TGFβ1 alone had positive effects on expression of ECM components under normoxia, whereas a positive effect of IGF1 in combination with TGFβ1 was only seen under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 98%
“…have argued that hypertrophy and expression of osteogenic markers after BMP2 stimulation might be more relevant when using MSCs than human articular chondrocytes. 29 Still, the role played by BMP2 in the CDMB deserves further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…In vitro , chondrocyte redifferentiation was supported by COL2A1, ACAN, and GAG biosynthesis. 45 Changes in the COL2A1, ACAN, and GAG levels therefore reflect the anabolic level of the cartilage ECM. 46 In this study, compared with the control group, the groups with IL-1Ra and miR-140 overexpression each individually presented with increased GAG accumulation in the cell supernatants and COL2A1 and ACAN expression in the chondrocyte, and the joint IL-1Ra and miR-140 treatment significantly enhanced these effects.…”
Section: Discussionmentioning
confidence: 99%